Com-educational Platforms: Creativity and Community for Learning - Iván Sánchez-López; Amor Pérez-Rodríguez; Manuel Fandos-Igado (Springer, 2019)
Education is at a time of redefinition and transformation, in line with an era characterized by considerable technological development and profound social changes. One would expect it to be accompanied by a media context in which narrative models are transformed by the impact of digitalization, affecting student-teacher interactions. However, it has been observed that the media usage of an entire generation emphasizes the gap between formal education and young people's everyday digital life. Within this framework, and at the international level, a series of innovative pedagogical proposals have emerged, which approach education from the field of communication: Minecraft Education, NFB Education, Educ'Arte, Scratch and 7 de Cinema. We have called them com-educational platforms, because of their investment in the education-communication vector, based on an educommunicative idea. The proposed study implements a multimodal discourse analysis (MDA) to gain an in-depth knowledge of its characteristics. Beyond their individual idiosyncrasies, our analysis reveals a common central feature: the placement of community-creativity combination as the core phenomenon for learning.